Effect of Fiber Position and Orientation on Flexural Strength of Fiber-Reinforced Composite - Ramin Mosharraf; Pirooz Givechian (Islamic Dental Association of Iran, 2012)
Background and Aim : One of the most important factors for increasing flexural strength of fiber-reinforced composite (FRC) restorations is the orientation, volume and geometry of reinforcement fibers. The aim of this study was to determine the effect of fiber position and orientation on the flexural strength of FRC specimens . Materials and Methods : In this experimental-laboratory study, five groups (N=8) of test specimens made of one indirect composite were reinforced with pre-impregnated fibers in different positions, orientations or geometry into the rectangle cube specimens (3×3×25mm3). The control group did not contain fiber reinforcement. The test specimens were stored in distilled water for 1 week at 37 ° C before testing in a three-point loading test with 1mm/min cross head speed. Data were statistically analyzed at 0.05 significance level with Kruskal-Wallis and Mann-Whitney tests . Results: The mean flexural strength of six experimental groups had significant differences (p1=0.005 and p2 < 0.001). The control group showed the lowest initial and final values. The maximum initial flexural strength was seen in the tension group (76.2 MPa) and the maximum final flexural strength was seen in the middle horizontal group (173.9 MPa). Conclusion : Within the limitations of this study, it may be concluded that the position and orientation of the fibers influenced the flexural strength of the fiber-reinforced composites and the most effective position of the fibers was tension side reinforcement .